PENGARUH PROMOSI, FITUR LAYANAN, DAN KEMUDAHAN TRANSAKSI TERHADAP KEPUTUSAN MENGGUNAKAN E-WALLET LINKAJA SYARIAH - Nurdiana, Tatia; Kusuma, Melia (JURNAL ILMIAH EDUNOMIKA, 2025)
The surge in online transactions has prompted the development of many innovative technologies in the financial industry, including the online payment application LinkAja Syariah. Several variables impact the choice to utilize the LinkAja Syariah e-wallet, including incentives, service features, and transaction convenience. This study seeks to ascertain the extent of effect that promotion, service features, and transaction convenience exert, both individually and together, on the choice to utilize the LinkAja Syariah e-wallet. This research employs a quantitative strategy utilizing a descriptive approach. A total of 100 respondents were surveyed. Employing the random sampling technique. Data analysis with multiple linear regression utilizing the IBM SPSS 26 software. This study found that promotional factors, service features, and transaction convenience had a favorable and substantial effect, both individually and together, on the choice to utilize the LinkAja Syariah e-wallet.